Adaptation of a Sensory Reactivity Assessment for Use With Children in the Western Cape Province, South Africa - Ann Frances Watkyns; Lizahn Gracia Cloete; Linda Diane Parham (Hindawi-Wiley, 2024)
Conclusion: A detailed methodology was developed to adapt a SR assessment for use in the Western Cape Province. Challenges in using the assessment were elicited primarily from community members rather than professionals.